Imagens em livros didáticos de química do início do século XX: a cuba pneumática - Crecchi, Renata Mourão (2009)
The present work focuses on illustrations of the pneumatic trough used by Lavoisier. Verify its role as an icon of modern chemistry. For this purpose we have analysed images of this apparatus presented in chemistry textbooks printed during the first half of XX century, regarding its relations to the text and also to ideas concerning the origins of modern chemistry. The selected primary sources include the Traité Elementaire de Chimie de Lavoisier and some Brasilian chemistry textbooks that were available in the first half of the XX century, such as: Noções de Chimica Inorganica (1875) by João Martins Teixeira; Traité Élémentaire de Chimie (1910) de Troost & Ed Pechard; Lições de Chimica (1915) and Chimica Geral Chimica Organica Analyse Chimica (1915) by J. Basin; Elementos de Chimica Inorganica (1918 and 1921) by Tibúrcio do Amaral; Pontos de Chimica (1937) by Almeida Cousin